Near-atomic resolution structures of interdigitated nucleosome fibres - Zenita Adhireksan (Nature Portfolio, 2020)
Crystal structures of nucleosome fibres assembled from cohesive-ended dinucleosomes with and without linker histone reveal open zigzag conformations that are interdigitated with one another, and suggest the role that linker DNA plays in observed variable fibre configurations and packing.